2021
DOI: 10.1155/2021/8843218
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Hepatic Encephalopathy Using Dunaliella salina Microalgae in Rats: Modulation of Hyperammonemia/TLR4

Abstract: Hepatic encephalopathy (HE) is a neuropsychiatric disease that is developed as a complication of both acute and chronic liver failure affecting psychomotor dysfunction, memory, and concentration. This study is aimed at evaluating the therapeutic effects of Dunaliella salina (D. salina) microalgae in thioacetamide- (TAA-) induced HE in rats. HE was induced by TAA (200 mg/kg; i.p.) for three successive days. Forty male Wister albino rats were divided into 4 groups; the first group was served as a normal, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Furthermore, impaired hepatic function and loss of liver ability to detoxify toxins are associated with lower levels of total protein and higher levels of ammonia. This agrees with Abdelgawad et al ( 2019 ) and El-Baz et al ( 2021 ) who indicated that impaired liver function decreases the total protein and elevates the levels of ammonia in the blood that crosses the blood-brain barrier and is metabolized in the brain astrocytes to glutamine. Indeed, ammonia interacts with other factors to disturb brain function (Butterworth 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, impaired hepatic function and loss of liver ability to detoxify toxins are associated with lower levels of total protein and higher levels of ammonia. This agrees with Abdelgawad et al ( 2019 ) and El-Baz et al ( 2021 ) who indicated that impaired liver function decreases the total protein and elevates the levels of ammonia in the blood that crosses the blood-brain barrier and is metabolized in the brain astrocytes to glutamine. Indeed, ammonia interacts with other factors to disturb brain function (Butterworth 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…The administration of Dunaliella salina showed to revert liver disfunction, decreasing inflammation and oxidative stress by its anti-inflammatory and antioxidant properties, as it was observed in thioacetamide- (TAA-) induced hepatic encephalopathy rat model [ 161 ].…”
Section: Microalgae-bioactive Compounds a Natural Source Of Potential...mentioning
confidence: 99%
“…El-Baz et al. showed that D. salina hydrochloride increased HSP25 and improved brain histopathological changes in HE patients, benefiting ALF prognosis ( 70 ).…”
Section: Types and Functions Of Damps Related To Aclfmentioning
confidence: 99%
“…In the study of Vidyasagar et al, serum HSP25 and HSP27 had antioxidant effects in ALF and CLF patients and reduced the damage caused by reactive oxygen species (ROS) and prevented the occurrence of HE (69). El-Baz et al showed that D. salina hydrochloride increased HSP25 and improved brain histopathological changes in HE patients, benefiting ALF prognosis (70).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%